Electrodeposition of compact Ag–Ni films from concentrated chloride baths and their test in the reduction of nitrate in alkali. (20th June 2020) - Mattarozzi, Luca; Cattarin, Sandro; Comisso, Nicola; El Habra, Naida; Guerriero, Paolo; Musiani, Marco; Vázquez-Gómez, Lourdes
Abstract: Compact Ag and Ag–Ni alloy layers have been electrodeposited from a concentrated chloride bath. The composition of the alloy can be controlled by regulation of the deposition current density j dep under conditions of accurate transport control like those ensured by the rotating disk electrode. XRD analyses suggest formation of Ag-rich crystalline phases in all samples and of Ni-rich crystalline phases only in samples with Ni fraction ≥50 at%. Test experiments of nitrate reduction in alkali show: almost exclusive reduction to nitrite on Ag; prevalent reduction to ammonia on Ni, with an important side evolution of hydrogen; predominant and more efficient reduction to ammonia on Ag–Ni, with lower hydrogen evolution and better current stability. Graphical abstract: Image 1 Highlights: Electrodeposition of compact Ag–Ni alloys from simple chloride baths. Accurate tuning of composition by regulation of the deposition current density. No substantial inclusion of foreign elements. Exploration of the performances as cathode for nitrate reduction.